Influência da manobra postural ativa e do diabetes mellitus tipo 2 na variabilidade da frequência cardíaca de homens de meia idade - Moura, Sílvia Cristina Garcia de (2012)
OBJECTIVE Evaluate the heart rate variability (HRV) of individuals with Type 2 diabetes, in the supine and in response to active postural maneuver from the supine to orthostatic position, by means of linear and non linear analysis and correlate these data. RESEARCH DESIGN AND METHODS Sixteen men with type 2 diabetes (DM) and sixteen control subjects (CG), age-range from 40 to 65 year were studied. The R-R intervals were recorded with a Polar RS800CX for 10 minutes in supine and 10 minutes in the orthostatic position. We assessed HRV using spectral (LFnu, HFnu and LF/HF), symbolic (0V%, 1V%, 2LV% and 2ULV%) analysis, Shannon (SE) and conditional entropy (complexity Index - CI and Normalized Complexity Index- NCI). RESULTS The DM presented higher sympathetic modulation (LFnu) in the supine position than the CG. In active postural maneuver for the variables LFnu and HFnu, DM showed no significant responses. Irrespective of position DM presented lower complexity than CG for SE. The same did not occur with conditional entropy, however, in both groups a reduction in values of entropies was observed with postural change. The reduction in complexity observed by SE was related to an increase in sympathetic modulation (0V%). CONCLUSION Our study showed that DM had higher sympathetic modulation in the supine position, which may be related to less complexity of HRV in this population. In addition, DM did not present the expected response of the autonomic nervous system to active postural maneuver for the variables LFnu and HFnu.